Topical cyclosporine A and interferon alpha-2b as adjuvants to surgery to decrease pterygium recurrence - Usha K Raina; Banu Pavitra; Shruti Bhattacharya; Kumar Ravinesh; Ruchi Goel (Oman Journal of Ophthalmology, 2023)
BACKGROUND: Pterygium is very common in India and is usually removed by limbal conjunctival autograft transplantation (LCAT), which, despite being the first-line therapy, is still associated with recurrences of up to 18%. OBJECTIVES: To compare the safety and efficacy of topical cyclosporine A (CsA) and interferon (IFN) alpha-2b in the prevention of postoperative recurrence of pterygium. METHODS: A total of 40 patients with primary pterygium were randomized into two equal groups, Group C and Group I. Both the groups underwent LCAT, with Group C kept on topical cyclosporine 0.05% (CsA) 4 times daily and Group I on topical IFN alpha 2b 0.2 million IU 4 times daily postoperatively for 3 months. Pre- and posttreatment best-corrected visual acuity (BCVA), recurrence, and complications were assessed at day 1, week 1, 1 month, and 3 months. RESULTS: The mean preoperative BCVA of 0.51 ± 0.18 and 0.51 ± 0.23 improved to 0.13 ± 0.13 and 0.13 ± 0.13 in Group C and Group I, respectively, after 3 months of treatment (P < 0.0001). Recurrence was seen in 2 cases in Group C and in 1 case in Group I at 3 months. No significant complications occurred in either of the groups. CONCLUSION: Topical CsA and IFN Alpha-2b are newer efficacious adjuvants with LCAT for prevention of postoperative pterygium recurrence.